PERAN KEPEMIMPINAN DALAM PENGELOLAAN KOPERASI SEKOLAH - Tri Desy Rahmawati; Nandha Cantika Khoirunnisa; Nindila Citra Ramdhani; Siswadi (STKIP Subang, 2026)
Economic education through school cooperatives plays a strategic role in shaping students' character and entrepreneurial skills. However, their management often faces challenges such as limited human resources and a lack of managerial competence. This study aims to analyze the strategic role of leadership in improving the effectiveness of school cooperative management. The research method used was a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation of school cooperative managers selected using a purposive sampling technique. Data analysis was conducted using an interactive model that included data reduction, data presentation, and conclusion drawing. The research results show that leadership is a key factor in the success of school cooperatives, where leaders serve as guides, motivators, and innovators. The leadership style deemed most effective is a combination of democratic, transformational, and participatory leadership. Despite challenges such as poor communication and transparency, solutions can be found through increased leadership capacity, open communication, and the use of information technology to strengthen management accountability. In conclusion, adaptive and visionary leadership is crucial for the sustainability of cooperatives as productive and modern economic learning platforms.